Mechanisms of absorption and elimination of drugs administered by inhalation. (August 2013) - Ibrahim, Mariam; Garcia-Contreras, Lucila
Pulmonary drug delivery is an effective route for local or systemic drug administration. However, compared with other routes of administration, there is a scarcity of information on how drugs are absorbed from the lung. The different cell composition lining the airways and alveoli makes this task extremely complicated. Lung cell lines and primary culture cells are useful in studying the absorption mechanisms. However, it is imperative that these cell cultures express essential features required to study these mechanisms such as intact tight junctions and transporters. In vivo, the drug has to face defensive physical and immunological barriers such as mucociliary clearance and alveolar macrophages. Knowledge of the physicochemical properties of the drug and aerosol formulation is required. All of these factors interact together leading to either successful drug deposition followed by absorption or drug elimination. These aspects concerning drug transport in the lung are addressed in this review.